Optimization and Characterization of Glycolipid Produced from Pseudomonas aeruginosa - A., Temaa A.; Hayder, Nadhem Hasan (Iraqi Journal of Science, 2026)
Rhamnolipids (RLs) are surface-active chemicals primarily generated by Pseudomonas aeruginosa and classified as glycolipid biosurfactants. They have attracted interest in several fields because of their unique properties. Therefore, this study aimed to extract, optimize and characterize the glycolipid from a clinical isolate of P. aeruginosa. One hundred-twenty specimens were gathered. Hemolysis test (primary screening) was performed to estimate the isolates that have the ability to produce biosurfactant (glycolipid). Only nine isolates of Pseudomonas spp. showed the highest hemolysis zones ranged between (26-40 mm), respectively. These isolates were subjected to secondary screening and emulsification index (E24%) to choose the best biosurfactant (glycolipid) produced isolate, whereas Pseudomonas sp. P30 isolate showed the highest E24% value, which was 60.6%, and was later subjected to the VITEK system, which confirmed this isolate was P. aeruginosa with a probability of 86%. Optimization of culture conditions was performed, and the results revealed that the best condition was when the isolate was cultured in mineral salt medium (MSM) containing olive oil and a mixture of NH4Cl and peptone as carbon and nitrogen sources at pH 7 and 72 hrs. of incubation. Four solvents were utilized to select the best solvent for glycolipid extraction, and the best solvent mixture was methanol: chloroform (1:2). Glycolipid was partially purified using silica gel column chromatography. In addition, Fourier transforms infrared (FTIR) spectrum and Fatty acid analysis (GC-Mass) used to characterize glycolipid. The study indicated that the biosurfactant extract was rhamnolipid.